Sistem Informasi Penjualan Tembakau Berbasis Web dengan Laravel: Implementasi Metode Waterfall dan Pengujian Black-Box - Anugrah, Harun; Setiawan Wibisono, Iwan (Jurnal Algoritma, 2025)
Tobacco sales by local businesses often face challenges in recording transactions and managing customer data. This study focuses on the design and development of a Laravel-based sales information system using the Waterfall methodology approach. The development of this system involves a series of processes that include needs identification, architecture design, design, testing, and system maintenance. This system contributes to the digitization of tobacco MSMEs with a time efficiency in recording of up to 45%. System testing indicates an increase in effectiveness in transaction data management and sales report presentation. With this system, it is hoped that business actors will achieve improvements in digitizing their business processes effectively and measurably.